Microbiome - Ravel, Jacques; Wellington, Elizabeth
The central purpose of Microbiome is to unite investigators conducting microbiome research in environmental, agricultural, and biomedical arenas. Topics broadly addressing the study of microbial communities, such as, microbial surveys, bioinformatics, meta-omics approaches and community/host interaction modeling will be considered for publication. Through this collection of literature Microbiome hopes to integrate researchers with common scientific objectives across a broad cross-section of sub-disciplines within microbial ecology.   Additional Instructions for Authors for Microbiome Nomenclature of organisms: Bacterial names should be written according to the guidelines of the American Society for Microbiology and the Journal of Bacteriology. Essentially, the names of all microbial taxa (kingdom, phyla, class, order, family, genus, species, and subspecies) should be italicized in the manuscript and the figures. Do not italicize strain designations or numbers.